Pendeteksian lightning dan thunderstorm pada area ruang udara bandara Jog/Wahh Adisutjipto International Airport dan Yogyakarta International Airport - Lukito, Indro; Pradnjaparamitha, Intan Dyah; Sudibya, Bambang; Dermawan, Denny (SENATIK STT Adisutjipto, 2020)
Daerah Istimewa Yogyakarta have Yogyakarta International Airport and  Adisutjipto International Airport to serve both of civil and military flight mission. Airport must be supported by weather information system for the flight safety. One of any methodes to detect bad weather is using radiosonde to record weather moving in every step of atmospheric level. Using indexes of weather detection can predict the developing weather and presented thunderstorm, lightning and any storm in both of airport area. The significant weather such as thunderstorm and lightning shall be a big danger for the flight which are located n its weather area and must avoid its area. The research focused to operating of radiosonde and how to analyze the becoming weather worst by calculating the weathar indexes of reported radiosonde recording. The result of its analyze is usefull for pilots especially in any steps of the flight, takeoff , approach and landing. Operating of radiosonde equipment which consist of ground equipment, antenna system, Global Positioning System, software of MGPS2, provided any transmission data that can be used to predict possibility bad weather and presented storm. The results of this research are lightning density in Weather Zone A Yogyakarta International Airport is      dA=17,97715 lightning/km2.yr with lightning threat level classified as “MIDDLE”. Lightning density in Weather Zone B Adisutjipto International Airport is dB=9,346163 lightning/km2.yr with lightning threat level classified as “LOW”. There were presented thunderstorm caused by high convection of heat in the atmosphere with possibility presented storm up to 75% in the bad weather condition.